2013
DOI: 10.1590/1678-7757201302138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxicity evaluation of granular magnesium substituted β-tricalcium phosphate

Abstract: Objective:The aim of this study was to produce dense granules of tricalcium phosphate (β-TCP) and magnesium (Mg) substituted β-TCP, also known as β-TCMP (Mg/Ca=0.15 mol), in order to evaluate the impact of Mg incorporation on the physicochemical parameters and in vitro biocompatibility of this novel material.Material and Methods:The materials were characterized using X-ray diffraction (XRD), infrared spectroscopy (FTIR), electron microscopy and inductively coupled plasma (ICP). Biocompatibility was assayed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 26 publications
9
28
0
Order By: Relevance
“…Our results showed that calcium/phosphorus content of DPSCs 1 b-TCP was significantly higher than that of DPSCs 1 nHAC/PLA. Tavares et al 56 reported that mitochondrial activity was similar between the MC3T3 pre-osteoblasts exposed to b-TCP extracts and the untreated cells using metabolic impairment tests, the results proved that b-TCP granules were able to release Ca 2 1 and PO 4 23 into media without cytotoxicity. It has been suggested that calcium phosphate biomaterials were resorbed in vivo in two ways: chemical dissolution and cellmediated degradation dissolution.…”
Section: Discussionmentioning
confidence: 85%
“…Our results showed that calcium/phosphorus content of DPSCs 1 b-TCP was significantly higher than that of DPSCs 1 nHAC/PLA. Tavares et al 56 reported that mitochondrial activity was similar between the MC3T3 pre-osteoblasts exposed to b-TCP extracts and the untreated cells using metabolic impairment tests, the results proved that b-TCP granules were able to release Ca 2 1 and PO 4 23 into media without cytotoxicity. It has been suggested that calcium phosphate biomaterials were resorbed in vivo in two ways: chemical dissolution and cellmediated degradation dissolution.…”
Section: Discussionmentioning
confidence: 85%
“…The main reflection for βTCP is located at 31.02° and the 2 1 7 plane in βMgTCP reflects at 31.06°. HAp displays its most prominent peak representing the 2 1 1 reflectance plane at 31.80°  34, 37, 38, 40 .
Figure 6Observed XRD Diffractograms and Rietveld Refinements for Heat Treated Atlantic Salmon Bone. Each inset displays the observed diffractogram on top followed by refinement results on bottom; diagnostic reflectance planes and corresponding 2 θ angles for each phase are indicated in the observed diffractograms; separated phases are presented in the refinement sections; hydroxylapatite (HAp) is represented in black, whitlockite (WH) in blue, and beta magnesium tricalcium phosphate (βMgTCP) in red; ( A ) salmon caudal vertebra heat treated at 500 °C demonstrating diagnostic reflectance peaks for WH and HAp; ( B ) salmon caudal vertebra heat treated at 600 °C demonstrating diagnostic reflectance peaks for βMgTCP and HAp; ( C ) well developed biphasic HAp-βMgTCP in a salmon caudal vertebra after treatment at 800 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for these results may be the direct contact between material and cells, which was the approach used by these authors. Tavares et al (2013) used a concentration of 100 mg mL -1 of bone substitute/medium in the assay of proliferation and cell viability. These authors found that β-TCP did not differ from control group after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot test was carried out to select which method of cell contact (direct or indirect) would be used, since both are found in the literature (Bernhardt, Lode, Peters, & Gelinsky, 2011;Doostmohammadi et al, 2011;Tavares, Castro, Soares, Alves, & Granjeiro, 2013;Vaziri, Vahabi, Torshabi, & Hematzadeh, 2012). The direct method provided higher rates of cell death compared to the indirect method, thus the latter one was chosen.…”
Section: Preparation Of Conditioned Mediummentioning
confidence: 99%